Pengaruh Dana Alokasi Umum, Dana Alokasi Khusus, Dan Pendapatan Asli Daerah Terhadap Belanja Daerah (Studi Empiris Pada Kabupaten/Kota Wilayah Jawa Tengah Tahun 2012-2014) - Penatari, Resi Intan; , Drs. Yuli Tri Cahyono , M.M., Akt., CA (2015)
In the local expenditure can't be loose from acceptance source, either balance of fund, regional loan, or regional income. Balance of fund is a funding sourced from APBN consisting of divide income fund, general allocation fund, and special allocation fund, while regional income is a funding sourced from regional. Purpose of this research is to get evidence empirically about the influence of DAU, DAK, and PAD with local expenditure. This research used quantitative research. In this research used taking sample method is saturation sample that is all of population made a research sample. Sample of this research amount to 29 regencies and 6 cities in Central Java Province. In this research used multiple regression analysis. Result of this research shows that DAU, DAK, and PAD influence significant statistic with local expenditure at the 0.05 rate of significancy. Keywords: General Allocation Fund, Special Allocation Fund, Regional Income, Local Expenditure